Price discovery and dynamics of Indian equity exchange traded funds. (2016) - Malhotra, Nidhi; Purohit, Harsh; Tandon, Deepak
The present study investigates the role of equity exchange traded funds (ETFs) in price discovery by studying a sample of nine equity ETFs following CNX Nifty and S&P BSE Sensex. The study reports an analysis based on the daily closing prices of ETFs and indices from the inception date of each ETF till December 2014. To examine the price discovery process, Johansen's cointegration test, vector error correction model (VECM), impulse response function and variance decomposition test are employed. The results depicts that both the ETF price series and index price series are non-stationary at levels but are stationary at first difference. Johansen cointegration test results reveal the existence of long term relationship for all ETFs except Most Shares M50. There is ample evidence to suggest that unidirectional causality between ETF prices and index prices. The results of VECM depicts that index prices lead the ETF prices and the presence of error-correction term restores the equilibrium in the long-run. The impulse response function results indicate that ETFs responds to index price variation and shock decay period ranges between two to three periods. The results underscores the role of ETFs in price discovery process and in India ETFs still behave as passive instruments for hedging purpose.